Brownian non-Gaussian polymer diffusion and queuing theory in the mean-field limit - Sankaran Nampoothiri; Enzo Orlandini; Flavio Seno; Fulvio Baldovin (New Journal of Physics, 2022)
We link the Brownian non-Gaussian diffusion of a polymer center of mass (CM) to a microscopic cause: the polymerization/depolymerization phenomenon occurring when the polymer is in contact with a monomer chemostat. The anomalous behavior is triggered by the polymer critical point, separating the dilute and the dense phase in the grand canonical ensemble. In the mean-field limit we establish contact with queuing theory and show that the kurtosis of the polymer CM diverges alike a response function when the system becomes critical, a result which holds for general polymer dynamics (Zimm, Rouse, reptation). Both the equilibrium and nonequilibrium behaviors are solved exactly as a reference study for novel stochastic modeling and experimental setup.